APPLE VINEGAR PRODUCTION BY FERMENTATION IN PILOT SCALE - Reyna M., Leoncio (2001)
Vinegar has been elaborated from apple juice by inmersed fermentation at room temperature. The process was developed in two stages, firstly, the alcoholic termentation was carried out using Saccharomyces Cerevísíae yeast, Ellipsoideus variety. Secondly, an acetic fermentation was carried out using acetobacter. The global yield of the process, based on row material usage was around 52%. The product obtained has an acidity of 6,8% in acetic acid and fulfill the market requirements.